Technique of Dietary Supplementation of Guanidinoacetic Acid for Growth Improvement of Catfish (Pangasius hypophthalmus) (Jurnal Ilmu-ilmu Perikanan dan Budidaya Perairan, 2023)
The present study aims to determine the best technique of Guanidinoacetic acid (GAA) supplementation to improve retention of added GAA after immersion in water on the growth performance of Pangasius catfish (Pangasius hypophthalmus). Pangasius catfish juveniles with a mean body weight and length of 16.05 ± 0.47 g and 12.42 ± 0.30 cm were randomly distributed into 9 pond units (2 x 1 x 0,6 m). Three experimental diets were formulated to contain (0,5% kg-1 GAA) with different technique of GAA supplementation, i.e. control, pelleting technique and spray-coating technique fed to the fish for 60 days of culture. The results showed that average body weight and biomass of fish fed diet with by GAA supplementation with the pelleting technique was higher (p